Odorless polymer latexes based on renewable protic ionic liquids for pressure-sensitive adhesives. Issue 1 (1st March 2014) - Mecerreyes, David; Adboudzadeh, M. Ali; Fernandes, Ana M.; Gracia, Raquel; Barandiaran, Maria J.; Moreno, Mónica
Abstract : Protic ionic liquid chemistry was used to develop green, odorless polymer latexes by incorporating commercially available dicarboxylic acids obtained from renewable sources. First, a series of protic ionic liquid monomers were synthesized by a straightforward proton-transfer reaction between renewable aliphatic dicarboxylic acids and 2-dimethylaminoethyl methacrylate. Free radical polymerization of these methacrylic protic ionic liquid monomers in water in the presence of a non-ionic surfactant was investigated. Stable polymer latexes were obtained in a narrow window of monomer solid contents and protic ionic liquid composition. Films of these latexes showed promising adhesive properties, in particular, in terms of peel resistance, which makes them good candidates for pressure-sensitive adhesives. Interestingly, due to the ionic nature of the monomers, the obtained latexes and the subsequent adhesive polymer films were odorless.